“The impact of motivation level of Small business owners on the financial performance of their firms” With special reference to Gampaha District. - Kularathne, M.A.D.T.S.P. (IJRDO - Journal of Business Management, 2015)
Successful small business activity is important for a healthy economy and can be a major sourceof job creation. While the concept of entrepreneurship has been around for quite some time,researchers continue to explore the factors that underlie small business financial performance.Specifically, researchers have sought to further examine why some small ventures are moresuccessful than others. The motivation has gained the attention of researchers and practitionersalike. Practitioners have realized that employees can no longer be perceived as biologicalmachines that are capable of leaving their feelings, norms, and attitudes at home when they goto work. Researchers are embracing the motivation because of its relationship with efficiency,productivity, sales, and revenues, quality of service, customer loyalty, employee recruitmentand retention and employee commitment.This study empirically examines the impact of motivation of small business owners on theirfinancial performance. The results of the study showed that motivation is at high level andfinancial performance is at moderate level. The Pearson‟s correlation analysis indicated thatthere is a strong positive correlation between motivation and financial performance. Theregression analysis indicated that there is a positive impact between motivation and financialperformance. The implication of the finding is high level of motivation positively correlatewith financial performance.